Synthesis and In Vitro Evaluation of New Thiosemicarbazone Derivatives as Potential Antimicrobial Agents - Zafer Asım Kaplancıklı; Mehlika Dilek Altıntop; Belgin Sever; Zerrin Cantürk; Ahmet Özdemir (Journal of Chemistry)
In an effort to develop potent antimicrobial agents, new thiosemicarbazone derivatives were synthesized via the reaction of 4-[4-(trifluoromethyl)phenyl]thiosemicarbazide with aromatic aldehydes. The compounds were evaluated for their inhibitory effects on pathogenic bacteria and yeasts using the CLSI broth microdilution method. Microplate Alamar Blue Assay was also carried out to determine the antimycobacterial activities of the compounds against Mycobacterium tuberculosis H37Rv. Among these derivatives, compounds 5 and 11 were more effective against Enterococcus faecalis (ATCC 29212) than chloramphenicol, whereas compounds 1, 2, and 12 and chloramphenicol showed the same level of antibacterial activity against E. faecalis. Moreover, compound 2 and chloramphenicol exhibited the same level of antibacterial activity against Staphylococcus aureus. On the other hand, the most potent anticandidal derivatives were found as compounds 2 and 5. These derivatives and ketoconazole exhibited the same level of antifungal activity against Candida glabrata. According to the Microplate Alamar Blue Assay, the tested compounds showed weak to moderate antitubercular activity.